3x+5=-65-4x

Simple and best practice solution for 3x+5=-65-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5=-65-4x equation:


Simplifying
3x + 5 = -65 + -4x

Reorder the terms:
5 + 3x = -65 + -4x

Solving
5 + 3x = -65 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
5 + 3x + 4x = -65 + -4x + 4x

Combine like terms: 3x + 4x = 7x
5 + 7x = -65 + -4x + 4x

Combine like terms: -4x + 4x = 0
5 + 7x = -65 + 0
5 + 7x = -65

Add '-5' to each side of the equation.
5 + -5 + 7x = -65 + -5

Combine like terms: 5 + -5 = 0
0 + 7x = -65 + -5
7x = -65 + -5

Combine like terms: -65 + -5 = -70
7x = -70

Divide each side by '7'.
x = -10

Simplifying
x = -10

See similar equations:

| 24c^3+4c^2-20c=0 | | 8.5=8.50x | | 3(5a+4)-8=19 | | (x-6)+(2x-6)=39 | | 30x+4=x | | -4x+8=6 | | 106-6x=12x+22 | | 6x+16=2x+40 | | -3p+8=-7p+-12 | | 14x-9=39-16x | | 2(-x+6)-(-1-x)+3x-8=4(10x-5)-14x+6+8-2x+7x | | 9Y-7=11+7Y | | 8(3+b+1)=4(b+3)-9 | | 7d+4=8+-d | | (3ym^7)=(11y^6m^4) | | 5(x+2)-4=16 | | -5g+9=-6 | | 2n+13=55 | | 2x+14=3x-6 | | X-5/2=-2 | | 13000.00+25000.00=213000 | | -49-2x=7-10 | | (x+10)(x-4)=-33 | | 0.5=m/120 | | 3(3y+2)+5=2(2y-2) | | 5x-1=2x+17 | | 2c+-13=5c+11 | | 7y+-9=-2y | | 1/14X+1/10X=1 | | 67-2x=43x+17 | | 3d+-5=7d+-9 | | -2j+6=j+-3 |

Equations solver categories